THE INFLUENCE OF ELECTRONIC MONITORING UTILIZATION OF BUDGET IMPLEMENTATION, ORGANIZATIONAL COMMITMENT, AND HUMAN RESOURCE COMPETENCE ON THE PERFORMANCE OF THE BUDGET IMPLEMENTATION (A SURVEY AT THE REGIONAL OFFICE OF THE MINISTRY OF RELIGION OF CENTRAL S - Hasanuddin, Hasanuddin; Amir, Andi Mattulada; Haris, Nurhayati (Master of Management Study Program, Faculty of Economics and Business, Tadulako University, 2021)
This research aims to examine the influence electronic monitoring utilization of budget implementation, organizational commitment, and human resource competence on the performance of budget implementation (A Survey at the Regional Office of the Ministry of Religion of Central Sulawesi Province). The data were collected through questionnaires and analyzed using the multiple linear regression method. The population in this research was all officials and staff related to budget management, as many as 52 people divided into 8 work units. The number of samples in this research was 43 respondents. The data analysis technique in this research used the IBM SPSS Statistics 21 program. The results show that using electronic monitoring of budget implementation, organizational commitment, and human resource competence simultaneously significantly affected budget execution performance. The results of the partial test show that the use of electronic monitoring of budget execution has a significant effect on the performance of budget execution, the partial test of organizational commitment has a significant effect on the performance of budget execution, and the partial test of human resource competence have a significant effect on the performance of budget execution. Keywords: Electronic Monitoring, Budget, Organizational Commitment, Human Resource Competence and Performance.